MPH Response Predictors in Attention Deficit Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
Response to methylphenidate (MPH) in 36 boys (7-12 years) with attention deficit hyperactivity disorder (ADHD) was examined in a double-blind, placebo-controlled, crossover study at the National Centre for Child and Adolescent Psychiatry, Oslo, Norway.